Gold nanoparticles-based sensors for detection of mycobacterium tuberculosis genomic DNA - Mansour, Amira Hazem (AUC Knowledge Fountain, 2016)
Tuberculosis (TB) caused by Mycobacterium tuberculosis (MTB), is an airborne disease that strikes one third of the globe’s population. In addition to infection of 9.6 million patients, TB claimed the lives of 1.5 million people in 2014 only. The majority of TB patients are present in the third world where the balance between cost-effective diagnostic method and prevalence of TB is difficult to achieve. Accurate diagnosis of TB is necessary to timely initiation of treatment. The available diagnostic tools are slow, while the rapid methods are either inaccurate or relatively unaffordable. So, sometimes the diagnosis is presumptive based on the clinical findings and the treatment is empiric. The treatment is lengthy and demands the administration of multiple antibiotics. However, the emergence of drug resistance threatened the global control programs of TB. The objective of this work is to develop cheap, fast and accurate detection methods. Two gold nanoparticles (AuNPs) based sensors were developed for colorimetric and fluorometric detection of MTB. Seventy two anonymous sputum samples were cultured then DNA was extracted. MTB H37Ra was the positive control while M. smegmatis and 8 non-MTB and negative controls. Characterization of the samples was achieved by multiplex PCR using MTB and NTM specific primers. Random samples were amplified by 16S-23S ITS primers and sequenced. Drug resistance associated mutations of MDR-TB were identified by MAS-PCR. The colorimetric assay aim was the detection of amplified MTB DNA by cationic AuNPs. The samples were amplified by IS6110 and rpoB primers. Only MTB samples yielded amplicons. So the negatively charged dsDNA attracted the positively charged AuNPs inducing their aggregation and the color turned blue. While the negative samples did not yield any amplicons and the AuNPs remained dispersed so the color was red. The sensitivity and specificity was 100% and the detection limit was 5.4 ng/μl of MTB DNA. The fluorometric assay exploited the quenching property of 40 nm AuNPs. The unamplified DNA was fragmented in the presence of 16s rDNA specific probe tagged with the fluorophore CY-3 by sonication and denatured for 3 min at 95 ºC followed by annealing at 52ºC for 45 sec. Then AuNPs were added and the fluorescence was measured. By FRET, the relative fluorescence was calculated revealing a cut-off value of 3. In MTB samples, the CY3-16s rDNA specific probe hybridized with its target and became spaced from the AuNPs allowing high fluorescence to be detected. Due to the lack of target-probe hybridization in the negative samples, the AuNPs were adsorbed on the probe and thus the fluorescence is quenched. Thirteen samples were chosen randomly, amplified and sequenced. Sequencing confirmed that 12/13 samples were MTB with 100% concordance with the multiplex PCR and FRET. The assay had sensitivity and specificity of 98.6% and 90% respectively and concordance of 98% with multiplex PCR. The detection limited was calculated to be 10 ng/ul. In conclusion, two AuNPs based sensors were developed to allow low cost and rapid detection of MTB on low source settings. The assays are rapid, sensitive and can have great potential in clinical practice for TB diagnosis.